Surface changes during turning of grey cast iron - Guesser W.L.* (2016)
© 2016 Inderscience Enterprises Ltd.The surface quality and the material near the surface are changed due to stresses induced by the machining process. In this work, surface and subsurface changes caused by turning of grey iron are studied. It was verified the formation of marks caused by the advancing edge of the cutting tool, material override, presence of debris on the surface and micro pores left by the fracture and pullout of graphite flakes. Thus, the surface roughness of the part is the result not only of the marks left by the cutting tool but also from the deformation and micro fractures that this surface undergoes during machining. In the region just below the machined surface it was observed intense plastic deformation of pearlitic matrix, causing thinning and expulsion of graphite through the surface and morphology change of sulphide particles. The implications of these surface features on the performance of the part are discussed.